2023
DOI: 10.1093/g3journal/jkad132
|View full text |Cite
|
Sign up to set email alerts
|

Using Drosophila to identify naturally occurring genetic modifiers of amyloid beta 42- and tau-induced toxicity

Ming Yang,
Matthew Zinkgraf,
Cecilia Fitzgerald-Cook
et al.

Abstract: Alzheimer’s disease (AD) is characterized by two pathological proteins, amyloid beta 42 (Aβ42) and tau. The majority of AD cases in the population are sporadic and late-onset AD (LOAD), which exhibits high levels of heritability. While several genetic risk factors for LOAD have been identified and replicated in independent studies, including the ApoE ε4 allele, the great majority of the heritability of LOAD remains unexplained, likely due to the aggregate effects of a very large number of genes with small effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 106 publications
0
1
0
Order By: Relevance
“…Multiple studies have demonstrated extensive variation in life span among the DGRP strains (26)(27)(28), consistent with aging heterogeneity in this collection of fly strains that can be leveraged to study age-dependent traits. Indeed, DGRP strains have been shown to vary widely in several parameters associated with aging, including visual senescence (29), decline in fecundity (27,30) and climbing ability (30,31) as well as susceptibility to neurodegeneration triggered by expression of pathogenic proteins such as Ab42 and tau (32) or mutant LRRK2 (33).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have demonstrated extensive variation in life span among the DGRP strains (26)(27)(28), consistent with aging heterogeneity in this collection of fly strains that can be leveraged to study age-dependent traits. Indeed, DGRP strains have been shown to vary widely in several parameters associated with aging, including visual senescence (29), decline in fecundity (27,30) and climbing ability (30,31) as well as susceptibility to neurodegeneration triggered by expression of pathogenic proteins such as Ab42 and tau (32) or mutant LRRK2 (33).…”
Section: Introductionmentioning
confidence: 99%